Phalloleucon abyssalis, a new cumacean genus and species (Crustacea: Peracarida: Leuconidae) from the Peru Basin - Mühlenhardt-Siegel, Ute (Zootaxa, 2008)
A new genus and species, Phalloleucon abyssalis, of the cumacean family Leuconidae from the Peru Basin is introduced. The new genus is characterised in having penial lobes and one pair of pleopods in males. It is suggested that the species Eudorella redacticruris Watling and McCann, 1997 is transfered into a new leuconid genus: Pseudeudorella.